(untitled) (Social Science Review, 2022)
Poetry has always been the noteworthy face of Iran’s cultural identity. Persian poets and their poems have reconstructed and revolutionized both the Eastern and Western literary world. Sadly, in a male-dominated Iranian society, female literary talents had been sidelined throughout centuries. Still, there were some iconic female poets who have blended their poetical talents with very powerful mental strength to cut off all the societal limitations, taboos and prohibitions and had left their marks on Persian literature’s history forever. But to attain that, they had to come across a long way. As the title indicates, the subject of this article is about the growth of some of those persistent women poets of Iran, with an emphasis on the hardships they have faced and how they overcame through those phases. In short, this article analyses the problems of women poets in the context of the socio-political environment of Iran and discuss the efforts the women poets have to made to break those barriers. The Central Library of Dhaka University, Departmental Library of Persian Language and Literature, DU and original Persian manuscripts from the authors personal collections are used as the primary resources for this article as well as online helpful websites. Social Science Review, Vol. 38(1), June 2021 Page 93-108